The first record of Evarcha pulchella (Thorell, 1895) (Araneae: Salticidae) from Pakistan with the first description of its female - Pir Asmat Ali (Journal of Insect Biodiversity and Systematics)
The jumping spider Evarcha pulchella (Thorell, 1895) (Salticidae) is recorded for the first time in Pakistan, based on material from the subtropical Hindu Kush dry meadows and hills. The female of this species is described for the first time. Detailed diagnostic illustrations and photographs of specimens are provided.